Fuel vapour recovery / Abdullah Syahril Mat Jani, Azrein Jamaluddin and Mohamad Fahmi Ghazali @ Mat Rol - Mat Jani, Abdullah Syahril; Jamaluddin, Azrein; Ghazali @ Mat Rol, Mohamad Fahmi (Faculty of Mechanical Engineering, 2001)
The first chapter explains on the literature review of this case study. What are research concern and the objective of this study. It also contains the history of what we have done and also the differences between both two stages. The second chapter are concerned about the Stage I of the fuel vapor recovery. It contains the regulations, types of methods in stage one and the conclusion. This chapter also has the trial project taken from Taiwan. Third chapter is on the Stage II of the Stages II fuel vapor recovery that highlight of it, the regulation and also the conclusion. This second stage has three methods of implementation and each of it has its own advantages and disadvantages. Fourth chapter is on the technical guidelines and the system design for the vapor recovery. The fifth chapter is on discussion for our research. In this chapter, we also have identified the problem that occurs when installing the fuel vapor recovery system. We also suggest several ideas to solve the problem so that the technology will be more viable. The final chapter is a conclusion chapter. We included our research project in this final chapter. We have summaries our findings, the analysis and our recommendations in carrying out the fuel vapor recovery.